Management of cryptococcal meningitis in a district hospital in KwaZulu-Natal: A clinical audit - Benjamin O. Adeyemi; Andrew Ross (AOSIS, 2014)
Background: Despite the development of context-specific guidelines, cryptococcal meningitis (CCM) remains a leading cause of death amongst HIV-infected patients. Results from clinical audits in routine practice have shown critical gaps in clinicians' adherence to recommendations regarding the management of CCM. Aim: The aim of this study was to review the acute management of CCM at an urban district hospital in KwaZulu-Natal, South Africa with a view to making recommendations for improving care. Setting: An urban district hospital in KwaZulu-Natal, South Africa. Methods: A retrospective audit was performed on clinical records of all patients (age > 13 years) admitted to the hospital with a diagnosis of CCM between June 2011 and December 2012. Results: Measurement of cerebrospinal fluid opening pressure at initial lumbar puncture (LP) was done rarely and only 23.4% of patients had therapeutic LPs. The majority of patients (117/127; 92.1%) received amphotericin B, however, only 19 of the 117 patients (16.2%) completed the 14-day treatment target. Amphotericin B-toxicity monitoring and prevention was suboptimal; however, in-patient referral for HIV counselling and testing was excellent. Conclusions: The quality of care of CCM based on selected process criteria showed gaps in routine care at the hospital despite the availability of context-specific guidelines. An action plan for improving care was developed based on stakeholders' feedback. A repeat audit should be conducted in the future in order to evaluate the impact of this plan and to ensure that improvements are sustained.